1996
DOI: 10.1021/jo960054k
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Elucidation of the Pentacyclopropane Antifungal Agent FR-900848

Abstract: Full structural elucidation of FR-900848, an antifungal pentacyclopropane nucleoside natural product from Streptoverticillium fervens, is reported. A series of model compounds were prepared using multiple asymmetric Simmons−Smith cyclopropanation reactions. Comparisons of spectroscopic data of synthetic alkenes 9 and 10, quatercyclopropanes 11 and 12, and imidazolidines 13 and 14 with FR-900848 and its degradation products 2, 3, and 4 were consistent with the full structural assignment of the natural product a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…[7][8][9][10] The total synthesis of FR-900848 1 [11,12] and U-106305 2 [12,13] was achieved in 1996 by Barrett et al, and the key step for the stereoselective assembly of the quatercyclopropane moiety was the enantioselective Simmons-Smith-type cyclopropanation of 2-butene-1,4-diol as developed by Charette et al [14] The higher acyclic and even cyclic syn-all-trans-oligocyclopropyl-1,n-dimethanol derivatives have been prepared not only as precursors to the natural products 1 and 2 but also out of interest in their conformational behavior. [15] Having gained some experience with the conformational analysis of bicyclopropyl early on, [16,17] we were intrigued by the conformational features of the quater-and quinquecyclopropane units in 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The total synthesis of FR-900848 1 [11,12] and U-106305 2 [12,13] was achieved in 1996 by Barrett et al, and the key step for the stereoselective assembly of the quatercyclopropane moiety was the enantioselective Simmons-Smith-type cyclopropanation of 2-butene-1,4-diol as developed by Charette et al [14] The higher acyclic and even cyclic syn-all-trans-oligocyclopropyl-1,n-dimethanol derivatives have been prepared not only as precursors to the natural products 1 and 2 but also out of interest in their conformational behavior. [15] Having gained some experience with the conformational analysis of bicyclopropyl early on, [16,17] we were intrigued by the conformational features of the quater-and quinquecyclopropane units in 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…To this end we envisioned the construction of aldehyde 48 via a directed cyclopropanation of a vinyl chloride. 30,31 The (S) enantiomer was initially selected for synthesis because it is derived from inexpensive D-mannitol. Cleavage of 1,2,5,6-di-O-cyclohexylidene-D-mannitol (49) using conditions developed by Schmid 32 cleanly provided protected glyceraldehyde 50 (Scheme 16).…”
Section: Synthesis Of the Phosphonate Side Chain 2smentioning
confidence: 99%
“…The structure of 1 including the absolute stereochemistry was established by degradation and synthetic studies to be as shown in Figure 1. 2 FR-900848 consists of a 2,4,14-octadecatrienoic acid having four contiguous and one isolated cyclopropanes, and a 5"-amino-5"-deoxy-5',6'-dihydrouridine. Closely related polycyclopropane compound U-106305 (2), a cholesteryl ester transfer protein (CETP) inhibitor, was isolated from Streptomyces sp.…”
mentioning
confidence: 99%
“…In the case of administration with [1-13 C]acetate, however, no incorporation was observed. Use of [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ]acetate which is expected to be more effective in detection of 13 C-enriched signals also failed to detect any incorporation. These results were unexpected since Kuo et al reported that structurally related long-chain cyclopropanoid 2 is biosynthesized via a polyketide pathway.…”
mentioning
confidence: 99%